Administration of Echinococcus granulosus protoscoleces by different ways in mice and detection of serological responses - Irehan, Bunyamin; Koroglu, Ergun; Simsek, Sami (Ankara Univ Press, 2016)
This study was planned for the aim of administration of hydatid cyst protoscoleces in Albino Balb/c mice in different ways for the formation of experimental hydatidosis and detection of serological response. For this purpose, the protoscoleces which were collected from sheep liver infected with hydatid cyst were divided into four experiments and one control group following to viability test. Protoscoleces were administrated by the way of intraperitoneal, subcutaneous, ocular and oral routes. In the control group, physiological saline was applied intraperitoneally. At the end of the experiment period (5 months) live mice were sacrified and some internal organs (lungs, liver, hearth, spleen, kidney and brain) were collected and those were examined both macroscopically and also microscopically by using of pathological tissue sections for hydatid cysts. Besides, blood samples were collected for the aim of the investigation of antibodies against hydatid cyst antigens by indirect-ELISA. On the 60th day of the study, sterile hydatid cysts which size of 2-2.5 cm diameter localized on right and left kidney of a died mouse were found in intraperitoneal group. Due to unable to complete the study process of mouse, serum samples couldn't be received. Sterile hydatid cysts were macroscopically detected in three mice in subcutan group and seropositivity was found by ELISA in all. It was observed neither macroscopic nor microscopic hydatid cysts in ocular group while seropositivity was detected in five mice. Similarly, neither macroscopic nor microscopic hydatid cysts were detected in oral group while seropositivity was observed in three mice. There was no any hydatid cyst formation and seropositivity in control group.
Farelerde echinococcus granulosus protoskolekslerinin farklı yollarla uygulanması ve serolojik yanıtın belirlenmesi
Keywords: Echinococcus granulosus; ELISA; experimental infection; hydatid cyst; mice